Analisis Tujuan Pengembangan Organisasi di SD Negeri 05 Surau Gadang di Kecamatan Nanggalo - Devina Maharani (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the objectives of organizational development at SD Negeri 05 Surau Gadang, Kecamatan Nanggalo. The research adopts a descriptive qualitative approach to identify the level of organizational development needs among teachers and staff. Data were collected using questionnaires and interviews, validated through mathematical testing and expert review. The results show that the majority of respondents have a moderate to high level of awareness regarding the importance of organizational development. The study concludes that organizational development at SD Negeri 05 Surau Gadang requires a more structured approach in human resource management and communication improvement. Recommendations are given for future organizational improvement strategies.